2006
DOI: 10.1016/j.solener.2005.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Solar gas turbine systems: Design, cost and perspectives

Abstract: The combination of high solar shares with high conversion efficiencies is one of the major advantages of solar gas turbine systems compared to other solar-fossil hybrid power plants. Pressurized air receivers are used in solar tower plants to heat the compressed air in the gas turbine to temperatures up to 1000°C. Therefore solar shares in the design case of 40% up to 90% can be realized and annual solar shares up to 30% can be achieved in base load. Using modern gas turbine systems in recuperation or combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(79 citation statements)
references
References 7 publications
0
66
0
8
Order By: Relevance
“…The CSP energy is used to either produce additional steam that is integrated in the NGCC's steam turbine to generate electricity [8], or to heat the compressed air in the gas turbine before entering the combustion chamber [16].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSP energy is used to either produce additional steam that is integrated in the NGCC's steam turbine to generate electricity [8], or to heat the compressed air in the gas turbine before entering the combustion chamber [16].…”
Section: Overviewmentioning
confidence: 99%
“…the solar multiple) in daily operation, annual performance, and economy of a DSG parabolic trough plant. Schwarzbözl et al [16] introduced and evaluated a system where solar tower plants use pressurized air receivers to heat the compressed air in a gas turbine. The system achieves an annual average solar to net electric efficiency of up to 19% which is amongst the highest conversion efficiencies for solar electric technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But between the injection cases, water injection into the combustor is preferable choice that has 7.1 years as capital payback period, the least energy production cost (0.054 $/kWh) and (À89.8 $) disadvantage (decrease in net incomes) respect to dry operation in compare to steam injection into combustor and recuperator. Peter Schwarzbozl et al [8] presented the performance and economic analysis of the solar hybrid gas turbine (1.4 MW e , 4.2 MW e and 16.1 MW e ) plants for two different locations and capacity factors. It was found that the total levelized electricity cost for stand-alone plant ranges from about 6.3 Vcent/kWh to 19.9 Vcent/kWh depending on power level and solar share.…”
Section: Introductionmentioning
confidence: 99%
“…The integrating of solar energy with conventional power plants or other power systems is an effective way to utilize solar energy and achieve fuel savings for power plant [5]. A higher solar efficiency can be obtained with solar-aided power generation (SAPG) than with solar only ones [6], and hybrid plants can use smaller solar fields, hence reducing the investment costs [7,8]. Typical values of energetic efficiency and land area for different types of parabolic trough solar-only plants can be found in [9].…”
Section: Introductionmentioning
confidence: 99%